2020
DOI: 10.1016/j.eclinm.2020.100569
|View full text |Cite
|
Sign up to set email alerts
|

Air pollution exposure at the residence and risk of childhood cancers in Denmark: A nationwide register-based case-control study

Abstract: Background The etiology of childhood cancer is poorly understood. The role of environmental factors, including air pollution (AP) exposure, has been addressed previously, but results so far have been inconclusive. In this study, we investigate the association between long-term AP exposures in relation to childhood cancer subtypes in Denmark (1981–2013). Methods We conducted a nationwide register-based case-control study. We identified 7745 incident cases of childhood ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(8 citation statements)
references
References 62 publications
1
6
0
1
Order By: Relevance
“…The crude and adjusted odds ratios (ORs) for exposure to PM 2.5 and sub-components and risk of childhood NHL are presented in Table 2. In correspondence with our previous publication [8], the adjusted OR and 95% confidence interval (95% CI) per IQR of PM 2.5 mass was 2.05 (1.10, 3.83) and 1.22 for BC (95% CI: 1.02, 1.46). We also observed an increased risk estimate for SIA (OR: 1.73, 95% CI: 0.68, 4.41), however with wide confidence intervals.…”
Section: Resultssupporting
confidence: 86%
See 2 more Smart Citations
“…The crude and adjusted odds ratios (ORs) for exposure to PM 2.5 and sub-components and risk of childhood NHL are presented in Table 2. In correspondence with our previous publication [8], the adjusted OR and 95% confidence interval (95% CI) per IQR of PM 2.5 mass was 2.05 (1.10, 3.83) and 1.22 for BC (95% CI: 1.02, 1.46). We also observed an increased risk estimate for SIA (OR: 1.73, 95% CI: 0.68, 4.41), however with wide confidence intervals.…”
Section: Resultssupporting
confidence: 86%
“…A recent Danish case-control study reported an association with maternal residential benzene exposure during pregnancy [7]. In a recently published study, we observed an association between residential exposure to ambient fine particulate matter (PM 2.5 ) during childhood and the risk of NHL in Danish children with an observed odds ratio (OR) of 2.11 (95% confidence interval, CI: 1.10, 4.01) per 5 µg/m 3 increments [8]. PM 2.5 , however, arises from various natural and anthropogenic sources and consists of a complex mixture of chemical components, of which some are released directly into the air (primary emitted) while others are formed by chemical reactions in the atmosphere (secondary).…”
Section: Introductionmentioning
confidence: 73%
See 1 more Smart Citation
“…Among the recognized risk factors are high and low birth weight (128) and sex, with boys more often affected than girls (129). Pesticide exposure (130,131), air pollution (132)(133)(134), paint (135), paternal tobacco smoking (136,137), and prelabour cesarean delivery (138) have been associated with an increased risk for ALL or AML but to date none of them is regarded as an established risk factor. There are also some factors that have been associated with a reduced risk for leukemia in the child, including maternal supplementation with folic acid or vitamins (139), or breastfeeding (140).…”
Section: Other Environmental Factorsmentioning
confidence: 99%
“…Em torno de 95% dos países mundiais, fazem parte de algum acordo que especifica a redução da poluição atmosférica (PNUMA, 2023). Contudo, muitos os negligenciam e desnaturam as condições de ar limpo impostas pelas autoridades mundiais, corroborando para maiores condições patológicas (FALKEMBACH, et al, 2003;HVIDTFELDT, et al, 2020).…”
Section: Resultsunclassified